Exploring the Role of Artificial Intelligence in Supporting Pre-Writing Skills and Academic Literacy: A Reflective Classroom Inquiry in an Islamic Educational Setting - Maulidiyah, Noor (Register Journal, 2025)
The integration of Artificial Intelligence (AI) into English language teaching and learning has transitioned from a mere innovation to an essential component of higher education. University students are increasingly utilizing AI-based applications to support them in various academic writing tasks, ranging from idea generation to language refinement. However, the application of AI tools during the EFL pre-writing stage remains underexplored. This descriptive qualitative research aims to investigate the types, functions, and purposes of the AI tools used during the pre-writing phase. Participants engaged in reflective writing, allowing them to articulate and assess their experiences with AI during this critical phase of academic writing. A thematic analysis was conducted, drawing from data provided by 50 undergraduate students at Antasari State Islamic University in Indonesia. The findings revealed that the most frequently utilized tool was ChatGPT, followed by Perplexity AI and DeepL. The study indicates that students mainly utilize AI tools for generating ideas, sourcing references, constructing outlines, enhancing linguistic accuracy, translating text, and improving time management and academic compliance. While these practices demonstrate the practical advantages of AI integration, they also raise significant ethical concerns. In particular, the excessive dependence on AI may diminish cognitive involvement, potentially impeding the growth of their academic literacy. Therefore, the findings emphasize the necessity of maintaining equilibrium between AI-assisted strategies and conventional pedagogical methods in academic writing instruction.